The Safavid EmpireThe Degradation of Political Islam - Muslimah , Elma; Basyir , Faris Abyan; Tabroni, Imam; Wei , Zhang; Kathryn, Morse (Journal Emerging Technologies in Education, 2023)
Background. After the end of the khulafaur rasyidin period, the history of Islamic civilization has been marked by the establishment of Islamic dynasties that played a role in the spread of Islam. However, after the Abbasid dynasty was destroyed by the Mongols, the light of Islam was dimmed. Purpose. Wars and struggles for Islamic power took place everywhere. Even the books of Islamic science were destroyed. Method. The political situation of Muslims as a whole only progressed again after the development of three major empires, namely the Ottoman Empire in Turkey, the Safawi Empire in Persia, and the Mughal Empire in India. Results. The name Safawiyah is known in Islamic history as the name of the kingdom located in Iran, before becoming the Safawiyah kingdom this kingdom originated from the tariqah movement in Ardabil, Azerbaijan (Russian territory) which was established simultaneously with the Ottoman Empire in Turkey. Named Safawiyah because it was taken from the name of its founder, Safi al-Din, the Safawiyah kingdom adheres to the Shia school as its state school. ConclusionThe founder of the safawiyah kingdom descended from the sixth Shia Imam. The fanaticism of the followers of the safawiyah order who opposed groups other than shia encouraged this movement to enter the political movement. The tendency towards politics emerged during the leadership of Junaid, who added political movements in addition to religious ones